Kesehatan Mental Siswa Laki-laki dan Perempuan Korban Bullying (Studi Kasus pada Siswa SD Negeri Di Kota Malang) - Salmiati, Salmiati; Hanurawan, Fattah (IAIN Syekh Nurjati Cirebon, 2023)
This research aims to determine the form, impact and differences in impacts experienced by male and female students who are victims of bullying on the mental health of elementary school (SD) students. So the focus of this research study is (1) the forms of bullying that occur in Malang City Elementary Schools (SD) (2) the impact on mental health (3) the differences in impacts experienced by male and female students who are victims of bullying. This research uses qualitative research methods with a case study type. The research subjects who were the targets of the research were 2 elementary school students who were victims of bullying, namely 1 boy and 1 girl, the parents of each of the two victims and the teacher at school. Data collection through interviews and observations. The research results revealed that the forms of bullying that occurred at the research location were (a) physical bullying in the form of pushing friends, hitting, taking things and fighting. (b) verbal form in the form of calling friends with bad names, threatening and shouting. (c) a form of relational bullying in the form of isolating and slandering. The impacts experienced by victims due to bullying behavior are stress, trauma, difficulty concentrating on studying, unstable emotional conditions (tantrums, frequent crying), difficulties in socializing, fear of socializing, shutting down, lack of self-confidence, likes to be alone, anxiety. the high one. In general, the impacts experienced by male and female students who are victims of bullying do not show any differences.Â Keywords: Mental Health, Bullying, Elementary School Students